Effect of Sn contents on thermodynamic, microstructure and mechanical properties in the Zn90-Bi10 and Bi88-Zn12 based ternary alloys - Esener, Pinar Ata; Altintas, Yemliha; Bayram, Umit; Ozturk, Esra; Marasli, Necmettin; Aksoz, Sezen (SPRINGER, 2019)
The thermal conductivity variations with temperature for Zn90-x-Sn-x-Bi10 (x=5,10, 40 and 85wt%) and Bi88-x-Sn-x-Zn-12 (x=1.39, 43.26 and 79.3wt%) alloys were measured by using the linear heat flow method. From thermal conductivity-temperature plots, the coefficients of thermal conductivity for the Zn-Sn-Bi alloys were calculated. The microstructures of Zn-Sn-Bi alloys were observed using scanning electron microscopy (SEM). The existing phases into microstructure were identified energy dispersive X-ray (EDX) analysis. The melting temperatures, the enthalpy of fusion and specific heat change between the liquid and solid phases in the Zn-Sn-Bi alloys were determined from Differential Scanning Calorimetry (DSC) trace. The tensile strength and microhardness of the alloys were measured using a Shimadzu Universal Testing Instrument (Type AG-10 KNG) and Future-Tech FM-700 model microhardness device.
Keywords: BI-SN; ZN; TEMPERATURE; ADDITIONS; Engineering; Materials Science; Physics